An improved chromosome sorting algorithm by permutation group-based inverted block-interchanges - Tabassum, Afrida; Abdullah, Wali Mohammad; Manjur, Najia; Islam, Rehennuma; Ahmed, Ashfaque Uddin; Morshed, Shourav Imtiaz; Tinni, Rizia Iqbal; Kabir, Kazi Lutful; Islam, Muhammad Nazrul (© 2016 IEEE, 2018)
This conference paper was published in the IEEE Xplore [© 2016 IEEE] and the definite version is available at : http://doi.org/10.1109/MEDITEC.2016.7835373 The Journal's website is at: http://ieeexplore.ieee.org/document/7835373/